KARAKTERISTIK SENSORIS PRODUK MINUMAN WHEY FERMENTASI DENGAN PENGGUNAAN PERSENTASE SUKROSA - Muhammad Taufik; Fatma Maruddin (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Whey dangke is a byproduct of the dangke industry and has not been utilized. The application of whey dangke to be a fermented beverage will provide functional and economical use values. Fermented whey products need to study the use of sugar in connection with future consumer preferences. Sucrose can be metabolized by microorganisms. The use of sucrose and the activity of microorganisms during fermentation can influence the sensory assessment of the final product of whey fermentation. The purpose of this research was to determine the sensory physical characteristics of fermented whey beverage products by adding various percentages of sucrose. The treatment in this research was the use of sucrose percentages of 3, 6, 9, and 12 % (w/v) and without the addition of sucrose and also using commercial products as a comparison. Sensory testing used 36 semi-trained panelists. Sensory assessment included sour taste, sweet taste, panelists' preference for aroma and appearance, and responsiveness of reception from panelists. The results showed that an increase in the percentage of sucrose causing whey fermentation of sour taste decreased, while the sweet taste, aroma and appearance preference increased. The panelist acceptance response to the sour and sweet taste of the fermented whey beverage product was the response received, while the panelist acceptance response to the aroma and appearance was from a neutral response to receiving. The used of 12% sucrose percentage in the processing of fermented whey drinks would produce drinks that are preferred by consumers. Keywords : whey dangke, fermentation, sucrose, sensory characteristics